Tetrads and polyads in Mimosa L. (Leguminosae): an overview on pollen diversity and evolution - Goicochea, Stefany Liau Kang (2022)
Mimosa L. has more than 500 species around the world, which have successfully adapted to the most varied ecosystems in their different forms of life, most of which are endemic. Despite the existence of innumerable studies at the macroscopic level, pollen morphology of Mimosa is known only to one-fourth of its more than 500 species (27.2%). The species already studied present variability as for the dispersion units, grain organization, ornamentation, and size, mainly. This work was divided in two parts: first, we studied the pollen of Mimosa species to understand if we have already reached the limits of known pollen diversity in the genus. Second, we mapped the most complete pollinic dataset to date over Mimosa\'s phylogeny to understand how pollen evolved in the genus. Although the pollen of more than 400 species is still unknown, our work increased knowledge on the morphology of Mimosa pollen, and filled existing gaps related to its evolution.